THE EVOLUTIONARY DIALECTIC OF NATURE: A STUDY IN RALPH WALDO EMERSON'S THE SNOW-STORM - Aida Thamer Salloom; Enas Jaafar Jawad (Journal of Higher Education and Academic Advancement, 2024)
The forefather of Transcendentalism or the American Romanticism that pervaded the political and literary scene of America in the mid-19th century, Ralph Waldo Emerson is a prolific and distinguished American essayist, lecturer, philosopher and poet. He strived to create a new American spirit, a new cultural basis and a heroic narrative that maintain an elevation of the American self. Though simple in their language and poetic diction, Emerson's essays and poems reflect his philosophical and thoughtful ideas in a dignified and melodious system. The study attempts to explore Emerson's appreciation to the dynamic, creative and evolutionary power of nature, advocating a unity between man and nature to help develop his intuition and regain his divine knowledge. Having a qualitative method, the study presents a reverent consideration to Emerson's essay Nature as a basic theoretical part for his concepts of the power of nature. A practical exemplification of Transcendentalism and the connectedness between nature and the human experience is thoroughly presented in the analysis of Emerson's poem "The Snow-Storm